A short review of honey supplementation on bone metabolism markers and sports performance - Wong, Chee Ping (UniSE Press, 2021)
Bee product such as honey has been used thousands of years ago as a healthy supplement among human being. Honey is a nutritious supplement and contains fructose, glucose amino acids and multivitamins-minerals. It is well documented that honey has antioxidant, anti-inflammatory, antimicrobial and anti-mutagenic properties. An antioxidant agent is proven able to prevent several acute and chronic disorders such as inflammatory, osteoporosis, osteoarthritis, cardiovascular and cancer. It is believed that honey is beneficial on bone health and sports performance but it is lacking solid scientific evidences to prove its efficacy. This article summarizes current evidences on the effects of honey supplementation on bone metabolism markers and sports performance.